Outcomes of early invasive treatment strategy in elderly patients with non-ST elevation acute coronary syndromes. Issue 10 (October 2016) - Conti, Elena; Musumeci, Maria B.; Desideri, Jasmine P.; Ventura, Martina; Fusco, Danilo; Zezza, Luigi; De Giusti, Marco; Berni, Andrea; Francia, Pietro; Volpe, Massimo; Autore, Camillo
Abstract : Background: As benefits of revascularization in non-ST elevation acute coronary syndromes (NSTEACSs) in the elderly are still unproven, we sought to assess the association between invasive or conservative management of NSTEACS and short-, mid- and long-term mortality or composite outcome of all-cause mortality and myocardial infarction in a cohort of consecutive elderly patients. Methods and Results: Consecutive NSTEACS patients older than 75 years discharged between 2006 and 2010 from a single intensive cardiac care unit, and managed with invasive or conservative strategy according to available guidelines were retrospectively surveyed. By multivariate regression and sensitivity analysis, crude and adjusted mortality and composite outcome were estimated at prespecified time points of short-term (in-hospital or 30 days mortality), mid-term (T1: 31 days to 6 months), and long-term (T2: 31 days to 12 months). A total of 453 patients (median age 80 years, 47% men) were evaluated; 301 (66.5%) underwent invasive treatment. Invasive was associated with significantly lower risk of short- [odds ratio (OR) 0.28, 95% confidence interval (CI) 0.12–0.67, P = 0.004], mid- (OR 0.33, 95% CI 0.16–0.67, P = 0.003) and long-term mortality (OR 0.34, 95% CI 0.20–0.58, P < .0001). Invasive strategy was also associated with nonsignificant lower short- (OR 0.55, 95% CI 0.28–1.07, P = 0.077), and highly significant lower mid- (OR 0.52, 95% CI 0.34–0.81, P = 0.003) and long-term adjusted cumulative composite outcome rate (OR 0.68, 95% CI 0.46–0.98, P = 0.004). Conclusion: In NSTEACS elderly patients, invasive strategy is independently associated with lower short-, mid- and long-term mortality and composite outcome.